الهوموسيستئين: عامل خطورة في الأمراض القلبية الوعائية في الساحل السوري - رضوان, فيصل; خدام, عقيل; أحمد, مريم (Latakia University Journal -Medical Sciences Series, 2019)
Cardiovascular disease is the leading cause of morbidity and mortality in the world and is one of the most common diseases worldwide. Considering that comes Homocysteine as independent risk factor, supported by a lot of studies that describe his relationship with cardiovascular disease, and this study aims to compare serum levels of homocysteine among cardiovascular disease patients and healthy people within the Syrian coast area. Study sample was divided into two groups; Patients group: included 44 patients who admitted for coronary angiography at Tishreen University hospital in Lattakia, patients had ≥50% stenosis at least in one major coronary artery, control group: included 44 patients had normal coronary arteries and no angiographic evidence of artery occlusion. The serum levels of homocystiene among the two groups of the study have been measured by the Chemiluminescence immunoassy technique(CLIA). The results showed a clear elevation in homocysteine values in patients group compared with the control group, where the average values (18.57versus 13.67µmol/l). ) (P-V<0.05). There was also a relationship between serum levels of homocysteine ​​and body mass index, where homocysteine ​​levels were found at> 25 kg / m² (P-V = 0.043) we hadn’t find relationship links serum levels of homocysteine with the number of stenotic major coronary arteries (one artery, two arteries, three arteries) in the patient group (P-V=0.281). In conclusion, necessity of measuring the serum level of homocysteine in ischemic heart disease patients especially newly diagnosed, that may help in more maximal management to the patient. يعد الداء القلبي الإكليلي السبب الرئيسي المؤدي للوفاة والعجز في العالم، وهو أحد أكثر الأمراض شيوعاً في العصر الحديث، ضمن هذا الواقع يأتي يأتي الهوموسيستئين كعامل خطر مستقل، مدعم ذلك بمئات الدراسات التي تصف علاقته مع أمراض الأوعية الإكليلية. تهدف هذه الدراسة إلى مقارنة المستويات المصلية للهوموسيستئين بين الأشخاص الأصحاء والأشخاص المصابين بالداء القلبي الإكليلي في منطقة الساحل السوري. تم تقسيم عينة البحث إلى مجموعتين؛ مجموعة المرضى: شملت 44 مريض من الذين خضعوا لتصوير الأوعية الإكليلية الظليل في مشفى تشرين الجامعي في مدينة اللاذقية، والذي أظهر تصوير الأوعية الإكليلية لديهم تضيق≥50%في شريان إكليلي رئيسي واحد على الأقل من الشرايين الإكليلية الرئيسية، مجموعة الشاهد: شملت44مريضاً من الذين أظهر تصوير الأوعية لديهم أن الشرايين الإكليلية سليمة ولا يوجد فيها أي لويحة عصيدية، وقمنا بدراسة المستويات المصلية للهوموسيستئين لدى مجموعتي الدراسة بطريقة المقايسة المناعية باللمعان الكيميائي، بالتوازي مع دراسة مجموعة من الخصائص السريرية والمعالم المخبرية ذات الصلة بالداء القلبي الإكليلي والهوموسيستئين. أظهرت النتائج ارتفاعاً واضحاً في قيم الهوموسيستئين لدى مجموعة المرضى بالمقارنة مع مجموعة الشاهد حيث كان متوسط القيم (18.577µmol/lمقابل 13.676). كما وجد علاقة بين المستويات المصلية للهوموسيستئين مع مشعر كتلة الجسم حيث وجد ارتفاع في مستويات الهوموسيستئين عند قيمBMI >25 kg/m² (P-V=0.043). ولم نجد علاقة تربط المستويات المصلية للهوموسيستئين مع عدد الشرايين الإكليلية المتضيقة (شريان واحد، شريانين اثنين، ثلاث شرايين) لدى مجموعة المرضى(P-V= 0.281). وبالنتيجة ضرورة إجراء معايرة للهوموسيستئين لجميع مرضى الداء القلبي الإقفاري خاصةً المشخصين حديثاً، مما قد يخدم في تدبير أكثر شمولية للمريض.